Penerapan Blended Learning dengan Pendekatan STEM untuk Meningkatkan Literasi Sains dan Kemampuan Kognitif Siswa SMA - Usemahu, Abdullah; Wally, Pramita; Marwah, Andi Sitti (Biosel Biology Science and Education, 2022)
Blended learning is a mixed learning model between face-to-face and online learning. The purpose of this study was to determine the influence and magnitude of the influence of the application of STEM-based blended learning on increasing scientific literacy and cognitive abilities and the responses of class XII students at SMA Negeri 11 Ambon in the new normal period. The type of research used was a pre-experimental design with one group pretest-posttest. The research was conducted at SMA Negeri 11 Ambon from December 2021 to January 2022. The research subjects were 36 students in class XII MIA-4 in the 2021-2022 academic year. The results showed that there was an effect of applying blended learning with the STEM approach to increasing scientific literacy and students' cognitive abilities. The average scientific literacy ability of students from the application of blended learning with the STEM approach has a percentage of 86.53% in the very high category, while students' cognitive abilities obtained an average N-gain value of 67.48% indicating that the use of blended learning models with the STEM approach is quite effective for improving cognitive outcomes in class XII students of SMA Negeri 11 Ambon. Keywords: Blended Learning, STEM, Literacy, Cognitive